1984
DOI: 10.1111/j.1432-1033.1984.tb08477.x
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise dissociation of yeast 60S ribosomal subunits by LiCl and identification of L25 as a primary 26S rRNA binding protein

Abstract: Treatment of yeast 60s ribosomal subunits with 0.5 M LiCl was found to remove all but six of the ribosomal proteins. The proteins remaining associated with the (26s + 5.8s) rRNA complex were identified as L4, L8, LIO, L12, L16 and L25. These core proteins were split off sequentially in the order (L16 + L12), L10, (L4 + L8), L25by further increasing the LiCl concentration. At 1 .O M LiCl only ribosomal protein L25 remains bound to the rRNA. Upon lowering the LiCl concentration the core proteins reassociate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 50 publications
2
29
1
1
Order By: Relevance
“…It contains dimethyllysine(s), trimethyllysines(s) (30), and methylarginine(s) (31). It can complex with rRNA in the presence of 0.5 M LiCl (32). Incubating the ribosome with 0.5 M NH 4 Cl generated the ribosome salt wash fraction in this study.…”
Section: Resultsmentioning
confidence: 97%
“…It contains dimethyllysine(s), trimethyllysines(s) (30), and methylarginine(s) (31). It can complex with rRNA in the presence of 0.5 M LiCl (32). Incubating the ribosome with 0.5 M NH 4 Cl generated the ribosome salt wash fraction in this study.…”
Section: Resultsmentioning
confidence: 97%
“…Although the differences between these two 60S localization assays may seem minor, they have the potential to identify a different set of factors required for ribosomal subunit assembly and export. Because Rpl25 binds directly to the rRNA, it is likely to be buried within the 60S ribosomal subunit (El-Baradi et al, 1984, 1987Yeh and Lee, 1998). Rpl11 binds later in ribosome assembly and appears to be located at the surface of the 60S ribosomal subunit (Tsay et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that three large-subunit r-proteins on mature 60S subunits can exchange in vivo, and the exchangeability of Rpl10p/Qsr1p, in particular, which is required for 60S to 40S subunit joining, suggests the possibility of an additional translational regulatory mechanism (46,209). Due to the lack of in vitro reconstitution assays for eukaryotic ribosomes, the abovementioned studies could only be complemented by approaches that examined the abilities of the different r-proteins to either bind to pre-rRNA molecules in vitro (204) or dissociate from purified ribosomal particles by increasing concentration of ions (52,106). The affinity of r-proteins for pre-rRNAs and the release of r-proteins by increasing concentration of ions are in general agreement with the order of their association with the preribosomal particles during in vivo ribosomal subunit assembly.…”
Section: Factors Involved In Ribosome Assembly?mentioning
confidence: 99%